2006
DOI: 10.1373/clinchem.2005.063206
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of RNA in Saliva

Abstract: Background:We have previously shown that human mRNAs are present in saliva and can be used as biomarkers of oral cancer. In this study, we analyzed the integrity, sources, and stability of salivary RNA. Methods: We measured the integrity of salivary RNA with reverse transcription followed by PCR (RT-PCR) or RT-quantitative PCR (RT-qPCR). To study RNA entry sites into the oral cavity, we used RT-PCR analysis of salivary RNA from the 3 major salivary glands, gingival crevice fluid, and desquamated oral epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
161
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(170 citation statements)
references
References 29 publications
6
161
0
3
Order By: Relevance
“…We have observed that similar to plasma the endogenous cell-free mRNA in saliva is protected from immediate degradation [13,14]. Meanwhile, the salivary mRNA finding has been challenged by others unable to detect mRNA in saliva supernatant and also not in whole saliva [15].…”
Section: Salivary Transcriptomementioning
confidence: 88%
See 3 more Smart Citations
“…We have observed that similar to plasma the endogenous cell-free mRNA in saliva is protected from immediate degradation [13,14]. Meanwhile, the salivary mRNA finding has been challenged by others unable to detect mRNA in saliva supernatant and also not in whole saliva [15].…”
Section: Salivary Transcriptomementioning
confidence: 88%
“…Since our initial reports we have published and accumulated an abundance of additional supporting evidence, ranging from the characterization of salivary RNA [13], over assessing salivary RNA integrity by cDNA library analysis [21], to identifying and supporting the commercialization of an effective stabilizer of RNA in whole saliva, RNAprotect® Saliva (QIAGEN) [22]. Salivary cDNA library analysis showed that none of the 117 cloned mRNAs from saliva supernatant are from a pseudogene of contaminating genomic origin.…”
Section: Salivary Transcriptomementioning
confidence: 99%
See 2 more Smart Citations
“…The long history of consumption of rice as human food and the 10 results presented in the present manuscript together illustrate that small RNAs with perfect 11 complementarity to human genes are present in grain from a safely consumed staple crop, 12 therefore implying that dietary small RNAs do not exhibit oral activity to an extent that would 13 have a meaningful impact on human health. 14 15 Cooking and processing of foods may destroy endogenous RNA and DNA molecules, although 16 any remaining nucleic acids are likely to be digested after consumption due to low gastric pH 17 and due to pancreatic nucleases secreted into the intestine and those present in the saliva and 18 blood (Carver and Walker, 1995;Park et al, 2006). Less than 5% of nucleic acid catabolites are 19 used for de novo synthesis of nucleic acids and the remaining catabolites are utilized in other 20 biochemical reactions or undergo excretion in the urine and feces (Carver and Walker, 1995).…”
mentioning
confidence: 99%